(untitled) (Faridpur Medical College Journal, 2018)
The anticoagulant drug warfarin is a vitamin K antagonist, coumarin derivative which inhibits the synthesis of clotting factors II, VII, IX, and X, as well as the naturally occurring endogenous anticoagulant proteins C and S. Warfarin is still considered the mainstay of oral anticoagulant treatment, it is a difficult drug to manage due to its narrow therapeutic index. An inappropriate management of patients can lead to subtherapeutic or supratherapeutic levels, increasing the risk of thromboembolic episodes or hemorrhagic episodes, respectively. Common indications for the use of warfarin include stroke prevention in atrial fibrillation, preventing thrombus formation in patients with heart valves and treatment of venous thromboembolism. When warfarin therapy is initiated for venous thromboembolism, it should be given the first day, along with a heparin product or fondaparinux. The heparin product or fondaparinux should be continued for at least five days and until the patient’s international normalized ratio is at least 2.0 for two consecutive days. The international normalized ratio goal and duration of treatment with warfarin vary depending on indication and risk. Warfarin therapy should be stopped five days before major surgery and restarted 12 to 24 hours postoperatively. Bridging with low-molecular-weight heparin or other agents is based on balancing the risk of throm boembolism with the risk of bleeding. Faridpur Med. Coll. J. Jan 2018;13(1): 40-43